Counting small induced subgraphs satisfying monotone properties - Roth, M; Schmitt, J; Wellnitz, P (IEEE, 2021)
Given a graph property Φ , we study the problem #INDSUB(Φ) which asks, on input a graph G and a positive integer k , to compute the number #IndSub(Φ,k→G) of induced subgraphs of size k in G that satisfy Φ . The search for explicit criteria on Φ ensuring that #INDSUB(Φ) is hard was initiated by Jerrum and Meeks [J. Comput. Syst. Sci. 15] and is part of the major line of research on counting small patterns in graphs. However, apart from an implicit result due to Curticapean, Dell and Marx [STOC 17] proving that a full classification into “easy” and “hard” properties is possible and some partial results on edge-monotone properties due to Meeks [Discret. Appl. Math. 16] and Dörfler et al. [MFCS 19], not much is known. In this work, we fully answer and explicitly classify the case of monotone, that is subgraph-closed, properties: We show that for any non-trivial monotone property Φ , the problem #INDSUB(Φ) cannot be solved in time f(k).|V(G)|o(k/log1/2(k)) for any function f , unless the Exponential Time Hypothesis fails. By this, we establish that any significant improvement over the brute-force approach is unlikely; in the language of parameterized complexity, we also obtain a #W[1] - completeness result.